Pengaruh Motivasi Kerja dan Fasilitas Kerja Terhadap Kinerja Karyawan Pada PT Bahana Mitra Prima Tangerang Selatan - Ravi Ravi; Aden Prawiro Sudarso (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The research methods used are quantitative and associative methods. Data collection techniques in this research used observation techniques and questionnaires. Data obtained by a questionnaire with 70 employees as respondents. Questionnaire data testing was analyzed using SPSS version 25 calculations, using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, coefficients of determination, hypothesis tests and simultaneous tests. Based on the results of this research, it can be seen from the results of multiple linear regression analysis that the equation value Y = 29,832+ 0.123 X1 + 0.110 ) with work motivation and work facilities (independent variables) have a very strong level of relationship. Based on hypothesis testing using the t test between the variable providing work motivation (X1) and employee performance (Y), the result is tcount is greater than ttable (5,130 >1,995) with a significance level of 0.000 < 0.05. This shows that incentives have a significant effect on employee performance. Meanwhile, the t test between the work facility variable (X2) and employee performance (Y) resulted in tcount being greater than ttable (5,940 > 1,995) with a significance level of 0.000 <0.05. This shows that work facilities have a positive effect on employee performance, with a coefficient of determination value of 57.6% while the remaining 42.4% is influenced by other variables which were not researched and based on the f test between the variables providing incentives and work facilities on employee performance it was obtained the results of fcount > ftable = 21,719 > 2,740 with a significance level of 0.000 < 0.05, meaning that work motivation and work facilities influence employee performance at PT Bahana Mitra Prima South Tangerang.